Subjective age from childhood to advanced old age: a meta-analysis - Pinquart, Martin; Wahl, Hans-Werner (Psychology and aging, 2021)
The present meta-analysis analyzed how the gap between subjective age and chronological age changes across the life-span and whether the size of this gap varies across regions of the globe. In addition, we tested for sources of the national differences. A systematic search in electronic databases (PsycInfo, Medline, Google Scholar, PSYNDEX) and cross-referencing identified 294 studies (with mean age ranging from 8 to 105 years) that were included in random-effects meta-analyses. While children felt about 3 years or 34% older than their chronological age, older adults (60+ years) felt, on average, between 10.74 and 21.07 years or 13%-18% younger. Associations between chronological age and the size of proportional differences between subjective and chronological were best described as a quadratic relationship, while associations with the size of absolute differences could also be described as a linear relationship. The widening of the gap between subjective age and chronological age across adulthood was found in all continents. Although adults reported a relatively younger subjective age across the globe, these differences were strongest in North America, Western Europe, and Australia/Oceania, and weakest in Africa. The regional differences disappeared after statistically controlling for national levels of individualism-collectivism, power distance, preference for young people rather than older adults, and quality of life of older people.